4.

Resolver por series la ecuación diferencial

Lo primero que defino es que es una ecuación de segundo orden y lineal

.

.

2a(2)) + (6a(1) .Assume that y = Σ(n = 0 to ∞) a(n) x^n. Differentiating.Σ(n = 2 to ∞) n(n-1)a(n) x^(n-2) + Σ(n = 1 to ∞) 4na(n) x^n + Σ(n = 0 to ∞) 2a(n) x^n = 0. Write out extra terms so all begin at n = 2: (2a(0) .Σ(n = 2 to ∞) (n+2)(n+1)a(n+2) x^n . Re-index second series so that all of them have x^n as a factor: Σ(n = 2 to ∞) n(n-1)a(n) x^n . Substitute these into the DE: (x^2 .1) Σ(n = 2 to ∞) n(n-1)a(n) x^(n-2) + 4xΣ(n = 1 to ∞) na(n) x^(n-1) + 2 Σ(n = 0 to ∞) a(n) x^n = 0.6 a(3)) x + Σ(n = 2 to ∞) n(n-1)a(n) x^n . y' = Σ(n = 1 to ∞) na(n) x^(n-1) and y' = Σ(n = 2 to ∞) n(n-1)a(n) x^(n-2). Simplifying: Σ(n = 2 to ∞) n(n-1)a(n) x^n .Σ(n = 0 to ∞) (n+2)(n+1)a(n+2) x^n + Σ(n = 1 to ∞) 4na(n) x^n + Σ(n = 0 to ∞) 2a(n) x^n = 0.

+ Σ(n = 2 to ∞) 4na(n) x^n + Σ(n = 2 to ∞) 2a(n) x^n = 0....x^2)..] + a(1) [x + x^3 + x^5 + . the general solution is y = a(0) [1 + x^2 + x^4 + . . 4. 3. Combine like terms: 2(a(0) . and if n is odd.. -(n+2)(n+1)a(n+2) + (n^2+3n+2) a(n) = 0 ==> a(n+2) = a(n) [surprise!]. then a(1) = a(3) = a(5) = .x^2) + a(1) x/(1 .= a(0)/(1 ....a(2)) + 6(a(1) .a(3))x + Σ(n = 2 to ∞) *-(n+2)(n+1)a(n+2) + (n^2+3n+2) a(n)] x^n = 0... Equate like coefficients (keeping in mind that a(0) and a(1) are arbitrary): a(2) = a(0) a(3) = a(1) For n = 2... then this yields a(0) = a(2) = a(4) = . If n is even. .] . via geometric series.. Hence.